Grain features of SnAgCu solder and their effect on mechanical behaviour of micro-joints - Jicheng Gong; Changqing Liu; Paul Conway; Vadim Silberschmidt (2006)
SnAgCu alloy, which promises compatible properties with Sn-Pb solder, has been identified as one of the most potential Lead-free solders for electronic interconnections. However, due to the miniaturization of solder joints, a micro-joint of this material contains only few grains. In this case, the mechanical behaviour of solder alloys shifts from the polycrystal-based to single-crystal based. Since P-Sn, the matrix of SnAgCu solder, has a contracted body-centred tetragonal structure, its grains are expected to have anisotropic properties, which are important, the reliability of a micro-joint. The present paper studies the inelastic anisotropic behaviour of this material. In order to analyse the effect of grain features, solder joints at different size are formed under the different cooling rate. An in-situ shear test is then performed to correlate the mechanical behavior of a joint to its microstructural features. The results show that the decrease in the joint's dimension results in the diminishment of the number of grains, and that the inelastic behaviour of SnAgCu grains is orientation-dependent